Matthew Arnold - Stanley, Carleton Wellesley, 1886-1971 (Alexander lectures, 1938)
MATTHE\V ARNOLD is undoubtedly in poetry, and I believe also in some of his prose, a classic. Carleton Stanley shows the influence of Greek poetry and thought on Matthew Arnold in these lectures.